PROGNOSIS AND THERAPY WHEN ACUTE PROMYELOCYTIC LEUKEMIA AND OTHER “GOOD RISK” ACUTE MYELOID LEUKEMIAS OCCUR AS A THERAPY-RELATED MYELOID NEOPLASM - Richard A. Larson; Michelle Le Beau (Mediterranean Journal of Hematology and Infectious Diseases)
Treatment for a pre-existing condition using chemotherapy, radiation therapy, immunosuppressive therapy, or a combination of these modalities may lead to the devastating complication of therapy-related myelodysplastic syndrome or acute myeloid leukemia (t-MDS/t-AML), collectively known as therapy-related myeloid neoplasm (t-MN). This disorder arises as a direct consequence of mutational events induced by the primary treatment.  The outcomes for these patients have been historically poor compared to people who develop AML de novo.  Currently comprising 10-20% of all cases of AML, t-MN is relatively resistant to conventional leukemia therapies, and is associated with short survival times. Median life expectancy from diagnosis is about 8-10 months in most series. Although the spectrum of cytogenetic abnormalities in t-AML is similar to AML de novo, the frequency of unfavorable cytogenetics, such as a complex karyotype or deletion or loss of chromosomes 5 and/or 7, is considerably higher in t-MN.  Two distinct groups of patients with t-MN have been described. The more common subtype, seen in about 75% of patients, typically occurs 5-7 years after first exposure to alkylating agents or radiation, is often preceded by a myelodysplastic syndrome, and is frequently accompanied by clonal cytogenetic abnormalities such as the loss of all or part of chromosomes 5 or 7. Mutations of the P53 tumor suppressor gene are also common.  The risk is related to total cumulative exposure over time to alkylating agents. In contrast, among individuals who develop t-AML after treatment with topoisomerase II inhibitors, the latency period to the development of t-AML is often only 1-3 years, antecedent MDS is rare, and gene rearrangements involving MLL at 11q23 or RUNX1/AML1 at 21q22 are common. It is now well recognized that acute promyelocytic leukemia (APL) and other subtypes of AML with balanced translocations sometimes occur as a t-MN in patients who have previously received cytotoxic therapy or ionizing radiation therapy. In general, t-MN patients should be encouraged to participate in prospective clinical trials that are appropriately designed for other AML patients with similar cytogenetic abnormalities.  Patients who have an HLA-matched donor should be considered for allogeneic hematopoietic cell transplantation, although patients with favorable karyotypes such as t(15;17) and inv(16) may do well with conventional intensive chemotherapy.  This review will focus on these “good risk” therapy-related leukemias, i.e. those with APL or inv(16)/t(16;16) or t(8;21).